Pidana Pemidanaan Tindakan Bagi Anak Sebagai Pencurian Dengan Kekerasan (Studi Kasus Putusan Nomor 20/Pid.Sus-Anak/2020/PN Jkt.Pst) - Dadang Setiawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Panel of Judges of Court Number 20/Pid.Sus-Anak/2020/PN Jkt.Pst on the perpetrators of the crime of theft with violence committed by children in the Decision. However, the Panel of Judges based on legal facts as a form of social justice in the community, the Judge still stated that the child Muhammad Fadillah Alias Ambon had been proven legally and convincingly guilty of committing the crime of "theft with violence" as the second alternative charge. However, for the sake of fulfilling the best interests of the child for the growth and development of the child in accordance with the principles of child protection law, the Judge imposed guidance and treatment measures on Child Muhammad Fadillah Alias Ambon at the Social Welfare Institution (LPKS) under the Supervision of the Central Jakarta Class I Correctional Center for 6 months.Hakin has also been fair to the Child Defendant by determining that the period of arrest and detention that has been served by Child Muhammad Fadillah Alias Ambon is deducted entirely from the length of guidance and treatment measures imposed.